Women leadership for sustainability of community forest User Groups: a Gender Perspectives - Acharya, Keshav Raj (Advances in Social Sciences Research Journal, 2020)
Community forest user groups are considered as prominent institutions in Nepal for the sustainable forest management through the active involvement of local people. Community forestry has mandatory provision of at least half number of women representation in executive committee however there is no restriction for all women representation in such committee. This study was conducted in two community forest user groups namely Mahila Srijana Community Forest User Group ( only women leadership) and Betkholshi Community Forest User Group ( mixed Leadership by both men and women) in Hetauda Sub-metropolitan city of Makwanpur district to identify whether the women leadership has significant contribution on sustainability of community forests. Different 4 criteria, 26 indicators and 60 verifiers were used to measure the sustainability through household survey (n=58), focus group discussion (n=4) and meeting minutes analysis. Present study reveals that overall sustainability index (OSI) of all women leaded community forest user group (OSI=0.502) was insignificantly lesser than the CFUG with the leadership of both men and women (OSI=0.512) however forest management practices was found better in women lead community forest.